2011
DOI: 10.1111/j.1365-2885.2010.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of modulation of P‐glycoprotein and /or Cytochrome P450 3A on the pharmacokinetics and pharmacodynamics of orally administered morphine in dogs

Abstract: The influence of pretreatment with ketoconazole [cytochrome P450 3A (CYP3A) + P-glycoprotein (P-gp) inhibitor], elacridar (selective P-gp inhibitor) and rifampicin (CYP3A + P-gp inducer) on oral morphine pharmacokinetics and pharmacodynamics was investigated in experimental dogs. Seven beagles were used in a four-way crossover design. Morphine hydrochloride was administered orally (2.5 mg/kg) alone (control group CON) or after pretreatment with ketoconazole (group KETO), elacridar (group ELA) or rifampicin (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…One strategy that has been applied to try and increase oral bioavailability of opioids in dogs is to coadminister the opioid with drugs that modulate the metabolism of opioids, for example with a drug that is an inhibitor of the cytochrome P450 enzyme system in the liver (Kukanich and others 2011) or an inhibitor of P-glycoprotein (Gadeyne and others 2011), a drug efflux pump that may limit absorption of morphine through gut enterocytes. Unfortunately, these novel strategies have failed to yield positive results so far.…”
Section: Options For Medium-term Opioid Analgesia In Discharged Dogsmentioning
confidence: 99%
“…One strategy that has been applied to try and increase oral bioavailability of opioids in dogs is to coadminister the opioid with drugs that modulate the metabolism of opioids, for example with a drug that is an inhibitor of the cytochrome P450 enzyme system in the liver (Kukanich and others 2011) or an inhibitor of P-glycoprotein (Gadeyne and others 2011), a drug efflux pump that may limit absorption of morphine through gut enterocytes. Unfortunately, these novel strategies have failed to yield positive results so far.…”
Section: Options For Medium-term Opioid Analgesia In Discharged Dogsmentioning
confidence: 99%
“…Plasma and CSF concentrations of morphine were determined using a validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method, as previously described by Gadeyne et al [25] . Quality control (QC) and blank samples were analyzed together with each batch of incurred samples to check the extraction and LC-MS/MS procedure.…”
Section: Methodsmentioning
confidence: 99%
“…In dogs, both in vivo and in vitro studies identified ketoconazole to be P-gp inhibitor (Kuroha, Azumano, Kuze, Shimoda, & Kokue, 2002;Kuroha, Shirai, & Shimoda, 2004). It has been used as a probe to assess the effect of P-gp inhibition on pharmacokinetics and pharmacodynamics of morphine (IV, PO), fentanyl (IV) and methadone (PO) in greyhound and beagle dogs (Gadeyne et al, 2011;Kukanich & Borum, 2008;Kukanich & Hubin, 2010;KuKanich et al, 2005) . No significant changes in disposition of these opioids were found in all studies.…”
Section: Genetic Variations In Drug Transport Proteinsmentioning
confidence: 99%
“…No significant changes in disposition of these opioids were found in all studies. Prolonged and increased sedation has been observed in dogs treated with ketoconazole prior to morphine administration (Gadeyne et al., ).…”
Section: Introductionmentioning
confidence: 99%